2015
DOI: 10.1111/cas.12765
|View full text |Cite
|
Sign up to set email alerts
|

CD44 variant 6 is correlated with peritoneal dissemination and poor prognosis in patients with advanced epithelial ovarian cancer

Abstract: Cancer stem cells (CSCs) drive tumor initiation and metastasis in several types of human cancer. However, the contribution of ovarian CSCs to peritoneal metastasis remains unresolved. The cell adhesion molecule CD44 has been identified as a major marker for CSCs in solid tumors, including epithelial ovarian cancer. CD44 exists as a standard form (CD44s) and also as numerous variant isoforms (CD44v) generated by alternative mRNA splicing. Here we show that disseminated ovarian tumors in the pelvic peritoneum co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 39 publications
3
62
0
Order By: Relevance
“…Loss of cell adhesion via deregulation of CD44, CLDN4, and CLDN6, followed by increased migration and invasive capabilities through upregulation of MMP2 describes a pattern consistent with localized ovarian cancer cells transforming into metastasizing PC cells, and expands previous data showing that deregulation of proliferation and cell adhesion is a feature of malignant transformation in ovarian and peritoneal cancer [10-13, 19, 28]. Tjhay et al, for instance, have shown that disseminated ovarian tumors in the peritoneum contain highly enriched CD44v6-positive cancer cells and an increased number of CD44v6-positive cancer cells in primary tumors was associated with a shortened overall survival in stage III-IV ovarian cancer [29]. In a xenograft model, Haria et al found that DLX4, a transcription factor encoded by a homeobox gene, induced expression of CD44 in ovarian tumor cells, and inhibition of CD44 abrogated the ability of DLX4 to stimulate tumormesothelial cell interactions [30].…”
Section: Discussionsupporting
confidence: 75%
“…Loss of cell adhesion via deregulation of CD44, CLDN4, and CLDN6, followed by increased migration and invasive capabilities through upregulation of MMP2 describes a pattern consistent with localized ovarian cancer cells transforming into metastasizing PC cells, and expands previous data showing that deregulation of proliferation and cell adhesion is a feature of malignant transformation in ovarian and peritoneal cancer [10-13, 19, 28]. Tjhay et al, for instance, have shown that disseminated ovarian tumors in the peritoneum contain highly enriched CD44v6-positive cancer cells and an increased number of CD44v6-positive cancer cells in primary tumors was associated with a shortened overall survival in stage III-IV ovarian cancer [29]. In a xenograft model, Haria et al found that DLX4, a transcription factor encoded by a homeobox gene, induced expression of CD44 in ovarian tumor cells, and inhibition of CD44 abrogated the ability of DLX4 to stimulate tumormesothelial cell interactions [30].…”
Section: Discussionsupporting
confidence: 75%
“…In addition, no significant differences were observed in the number of cycles of chemotherapy and surgical debulking status between CD44v6-high and -low groups. Pathologically, there were 87 (46.8%) serous, 33 A total of 50 distant metastatic sites were identified in 37 of 186 (19.9%) patients. Twenty-five patients had distant metastatic disease at the time of diagnosis, consistent with M1 status, whereas 12 patients had distant metastases during relapse of progressive disease.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, 186 patients who were surgically treated with or without chemotherapy were included; 48 patients had been included in our previous study investigating peritoneal dissemination of ovarian cancer. 33 Patients with multiple primary cancers or nonepithelial tumors were excluded. Eligible patients were followed up until December 2014.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations